High-power electro-optic switch technology based on novel transparent ceramic - 张学娇 叶青 瞿荣辉 蔡海文 (Chinese physics B, 2016)
A novel high-power polarization-independent electro-optic switch technology based on a reciprocal structtire Sagnac interferometer and a transparent quadratic electro-optic ceramic is proposed and analyzed theoretically and experimentally. The electro-optic ceramic is used as a phase retarder for the clockwise and counter-clockwise polarized light, and their po- larization directions are adjusted to their orthogonal positions by using two half-wave plates. The output light then becomes polarization-independent with respect to the polarization direction of the input light. The switch characteristics, including splitter ratios and polarization states, are theoretically analyzed and simulated in detail by the matrix multiplication method. An experimental setup is built to verify the analysis and experimental results. A new component ceramic is used and a non- polarizing cube beam splitter （NPBS） replaces the beam splitter （BS） to lower the ON/OFF voltage to 305 V and improve the extinction ratio by 2 dB. Finally, the laser-induced damage threshold for the proposed switch is measured and discussed. It is believed that potential applications of this novel polarization-independent electro-optic switch technology will be wide, especially for ultrafast high-power laser systems.